2014
DOI: 10.1021/jp500113h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Facilitated by Monovalent Cations and Their Use as Efficient Dye Adsorbents

Abstract: Gelation behavior of lithocholate (LC(-)) mixed with different monovalent cations in water was detected. The hydrogels consisting of tubular networks were formed by introducing alkali metal ions and NH4(+) to lithocholate aqueous solutions at room temperature. The formation of tubular structures was considered to be mainly driven by the electrostatic interaction with the assistance of a delicate balance of multiple noncovalent interactions. It is interesting that the increase in temperature can induce a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…The dye concentration decreased sharply after the addition of xerogels, and then decreased gradually, reaching very low value after 30 min (Figure b). As shown in Figure a and b, all the MO content can be adsorbed almost completely within 5 h with a dye adsorption value of 158.9 mg⋅g −1 , which is an excellent result among the reports of other gels . Generally, the dye adsorbing agents should include two domains: hydrophilic domain to interact with water and hydrophobic domain to adsorb the dye ,.…”
Section: Discussionsupporting
confidence: 58%
“…The dye concentration decreased sharply after the addition of xerogels, and then decreased gradually, reaching very low value after 30 min (Figure b). As shown in Figure a and b, all the MO content can be adsorbed almost completely within 5 h with a dye adsorption value of 158.9 mg⋅g −1 , which is an excellent result among the reports of other gels . Generally, the dye adsorbing agents should include two domains: hydrophilic domain to interact with water and hydrophobic domain to adsorb the dye ,.…”
Section: Discussionsupporting
confidence: 58%
“…However, the overall effect on the aggregates depends on several factors such as hydrophobic and electrostatic interactions, electrolyte effects, hydrogen bonding interactions with the aggregates, counter ions and the water molecules, etc. [56][57][58][59] The TEM images of NaDC aggregates in the presence of different concentrations of IL are shown in Fig. 55 The modulation of the aggregated structure of NaDC in the presence of different wt% of IL can be confirmed by TEM and SEM measurements.…”
Section: Microstructuresmentioning
confidence: 74%
“…LCA is a secondary bile acid having a nearly planar steroid backbone and a carboxyl group linked to the steroid backbone through a short alkyl chain. It has been shown that negatively charged LCA in alkaline aqueous solution can self-assemble into tubular structures with different diameters and shapes, depending on experimental conditions [32]- [37]. Figure 3(a) is an AFM image of LCA nanotubes formed in NH 4 OH solution.…”
Section: Resultsmentioning
confidence: 99%